Genotoxicity and mutagenicity of water samples from the Monjolinho River (Brazil) after receiving untreated effluents - Bianchi, Jaqueline [UNESP]; Gaeta Espindola, Evaldo Luiz; Marin-Morales, Maria Aparecida [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Cytotoxicity, genotoxicity and mutagenicity assays, using the Allium cepa test-system, were carried out in order to evaluate the effects of domestic and industrial effluents in the Monjolinho River in different seasons of the year. In the summer and intermediate seasons, chromosome aberration, micronuclei, cell death and inhibition of the mitotic index were observed in water samples collected at different sites. In the winter, either chromosome or cellular alterations were not observed. Through chemical analysis, we infer that the excessive metals such as Pb, Ni and Cu were mainly responsible for the effects observed in A. cepa cells. Limnologic analysis like electrical conductivity, dissolved oxygen and the presence of nitrogen and phosphated compounds showed that the river's contamination is due to organic matter discharge along its course. Moreover we note that this river had a higher self-depurative capacity at the end of its course, before its confluence with the Jacare-Guacu River. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Allium cepa; Chromosome aberration; Micronucleus; Cytotoxicity; Aquatic toxicology